Pengaruh CAR, DPK, NIM, ROA, NPF, dan Inflasi terhadap FDR Bank Umum Syariah Indonesia Periode 2016-2020 - Khoirunisa Khoirunisa; Rendra Erdkhadifa (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The growth of the FDR of Indonesian Islamic Commercial Banks from 2016 to 2020 has decreased. The decrease was due to the easing of financing distribution in order to maintain the quality of financing. The FDR is in a low position, indicating the bank is in a liquid condition, but the bank'si function has not been fulfilled. This study aims to determine whether or not there is an effect of CAR, DPK, NIM, ROA, and Inflation variables on the FDR. This study uses quantitative methods of associative research. The data source uses secondary data from the financial statements of Indonesian Islamic Commercial Banks and Bank Indonesia inflation reports. Analysis of the data used is panel regression using Eviews. The results showed that the CAR and DPK variables had a significant effect on the FDR. While the variables NIM, ROA, NPF, and Inflation have no significant effect on the FDR.